Guatemala : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Context. Guatemala's economy has performed solidly since the 2008-09 crisis. Output has converged to potential, inflation is under control, and macroeconomic policies remain prudent. However, risks to the outlook are tilted downwards, while buffers are modest and space for counter-cyclical policies is thin. Long-term inclusive growth is constrained by low investment in physical and human capital, institutional weaknesses, and lack of security. Near-term policies are broadly appropriate. With the output gap closed, the broadly neutral fiscal stance is adequate. The monetary stance is slightly expansionary, but inflation is at the bottom of the target range. The authorities should stand ready to tighten monetary policy if inflationary pressures re-emerge. Fiscal sustainability should be enhanced over the medium term. Though the debt-to- GDP ratio remains moderate, the ability to implement counter-cyclical fiscal policies is limited, not least by Guatemala's high government debt-to-revenue ratio. Debt stabilization requires moderate tightening of the budgetary stance over the medium term. The emphasis should be on revenue mobilization, given the overall low level of spending. Consolidating gains from the 2012 tax reform, which has so far proved disappointing, will be critical. Efforts to upgrade the monetary and exchange policy framework should continue. Anchoring low and stable inflation will require measures to bolster monetary policy transmission, including by expanding exchange rate flexibility. This should provide an additional shock absorber and reduce incentives for dollarization. It would also establish the inflation target as the undisputed primary objective of the central bank. Further strengthening of the financial system is necessary. The 2014 FSAP update found that Guatemala has made significant progress in financial regulation and that the banking system appears to be generally sound. However, efforts are still needed to improve consolidated supervision and the regulation of off-shore banks. The time is also ripe for a phased move to Basel III standards. Structural reforms are vital to achieving long-term inclusive growth. Paving the way towards high, inclusive growth will depend upon raising the low tax-to-GDP ratio to support priority public spending, thereby addressing critical social and developmental needs.